Internet of Things (IoT) and its Contributions in Earthquake Disaster Management - Poudyal, Youba Raj (Journal of Physical and Life Sciences, 2024)
Earthquake disaster management seeks to mitigate the potential harm caused by disasters, provide prompt and appropriate aid to the victims, and achieve efficient and swift recovery. Earthquake disaster management is one of the several applications of the Internet of Things (IoT), a highly promising technology. The IoT plays a crucial and widespread role in earthquake disaster management, with the capacity to potentially rescue lives. This article examines the contribution of IoT in the management of natural disasters, specifically focusing on its application in earthquake disaster management. The IoT enabled swift and efficient responses in the management of natural disasters. The main purpose of IoT is to detect earthquake disasters and provide advance notification to the general public. The implementation of IoT can be achieved by broadcasting messages in a more accurate and intelligent manner to effectively communicate with the public. Data is initially gathered from the surroundings by a vibration sensor, and subsequently communicated, evaluated, and received by a receiver. The essential message is then sent to smart and GSM mobile devices. This study provides substantial contributions to the establishment of suitable frameworks for the IoT in the field of earthquake disaster management.